Pengaruh Penggunaan Video Pembelajaran dalam Liveworksheet terhadap Kemampuan Pemecahan Masalah pada Materi Perubahan Lingkungan - Mustika Fitri Nur; Darlen Sikumbang; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2022)
The research aimed to know the effect of using learning video in liveworksheet towards students’ problem solving ability at SMAN 1 Bandar Lampung on environmental change material for class X of the 2021/2022 academic year. The research design used in this study is the non-equivalent control group design. The research took sample of 72 students consisting of class X MIPA 4 as a control class and X MIPA 5 as an experimental class with purposive sampling technique. Problem solving ability data obtained from pretest-posttest were analyzed using the Independent sample t-test analysis technique. The results showed that at the 0.05 significance level, the Sig. value was obtained. (2-tailed) 0.004 0.05. So it can be concluded that there is a significant effect of the use of learning videos in live worksheets towards the problem solving abilities of students on the material of environmental change.Penelitian ini bertujuan untuk menganalisis pengaruh video pembelajaran dalam Liveworksheet terhadap kemampuan pemecahan masalah siswa di SMAN 1 Bandar Lampung pada materi perubahan lingkungan pada kelas X semester genap tahun ajaran 2021/2022. Desain penelitian yang digunakan dalam penelitian ini  adalah Non equivalent control group design. Sampel penelitian berjumlah 72 peserta didik yang terdiri dari kelas X MIPA 4 sebagai kelompok kontrol dan X MIPA 5 sebagai kelompok eksperimen dengan teknik pengambilan sampel purposive sampling. Data kemampuan pemecahan masalah dianalisis menggunakan teknik analisis Independent sample t-test. Hasil penelitian menunjukan bahwa pada taraf signifikansi 0,05 didapatkan nilai Sig. (2-tailed) 0,004 0,05 sehingga dapat disimpulkan bahwa terdapat pengaruh yang signifikan dari penggunaan video pembelajaran dalam liveworksheet terhadap kemampuan pemecahan masalah siswa pada materi perubahan lingkungan.Kata kunci: kemampuan pemecahan masalah, liveworksheet, video pembelajaran DOI: http://dx.doi.org/10.23960/jbt.v10i2.25076